Development and characterization of elephant foot yam starch–hydrocolloids based edible packaging film: physical, optical, thermal and barrier properties - Nagar, Mohit (J Food Sci Technol, 2019)
The study aimed at the development of elephant foot yam starch (EFYS) based edible film through blending of Xanthan (XG) and agar–agar (AA). Film thickness and density increased with increase in concentration of hydrocolloids and the respective highest value 0.199 mm and 2.02 g/cm(3) were found for the film possessing 2% AA. The film barrier properties varied with hydrocolloids and the lowest value of water vapour transmission rate (1494.54 g/m(2)) and oxygen transmission rate (0.020 cm(3)/m(2)) was observed for the film with 1% XG and 1.5% AA, respectively. Mechanical and thermal properties also improved upon addition of hydrocolloid. Highest tensile strength (20.14 MPa) and glass transition temperature (150.6 °C) was observed for film containing 2% AA. Fourier transform infrared spectroscopy demonstrated the presence of –OH, C–H, and C=O groups. The change in crystallinity was observed through peak in X-ray diffraction analysis, which increased with increase in the hydrocolloids’ concentration.